Update on the management of penile and meatal strictures. Issue 5 (September 2021) - Vetterlein, Malte W.; Fisch, Margit M.; Zumstein, Valentin
Abstract : Purpose of review: Treatment of penile and distal urethral strictures including the fossa navicularis and the meatus remains challenging due to their adverse etiology and lack of ventral tissue support. In this contemporary review, we summarize the available evidence and recent advancements in reconstructive techniques. Recent findings: Over the last years, several refinements of already established techniques have been added to the reconstructive armamentarium in the management of penile urethral strictures. These include the single-stage combination of flap and graft, the additional use of tissue glue, or an optimized single-stage tubularization using a free graft. Summary: There is a shift toward an increased use of single-stage procedures even in complex strictures of the penile and distal urethra. This is reflected by advancements and refinements in operative techniques. Nonetheless, staged urethroplasty remains a cornerstone of curative management in such patients with durable success rates. Future research should focus on identifying distinct patient and stricture characteristics to determine the individual therapeutic approach with optimal functional outcomes.